1985
DOI: 10.1007/bf00305977
|View full text |Cite
|
Sign up to set email alerts
|

Mutant genes affecting higher plant meiosis

Abstract: That meiosis is conditioned by a large number of genes majority of which are present in a dominant state, is evidenced by the detection of numerous monogenic recessive mutant genes which affect the premeiotic, meiotic and post-meiotic course of events. These genes are site- and stage-specific, and a few are sex specific. Of these, the most prevalent are the mutant genes affecting male meiosis and causing male sterility (ms genes) and those inhibiting synapsis and chiasma formation (synaptic genes) and leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 152 publications
2
94
0
Order By: Relevance
“…Extensive evidence obtained for different animal and plant species has demonstrated that each step of meiosis is genetically controlled (see Gottschalk and Kaul, 1974;Baker et al, 1976;Golubovskaya, 1979;Kaul and Murthy, 1985). Many meiotic mutants were found during these years, especially in maize (Albertsen and Phillips, 1981;Golubovskaya, 1989) and Arabidopsis thaliana (Dawson et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive evidence obtained for different animal and plant species has demonstrated that each step of meiosis is genetically controlled (see Gottschalk and Kaul, 1974;Baker et al, 1976;Golubovskaya, 1979;Kaul and Murthy, 1985). Many meiotic mutants were found during these years, especially in maize (Albertsen and Phillips, 1981;Golubovskaya, 1989) and Arabidopsis thaliana (Dawson et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…of the first meiotic mutant C(3)G in Drosophila, the genotypic control of meiotic process has been ex amined in several reviews (John and Lewis 1965, Riley 1966, Taylor 1967, Gottschalk 1968, Baker et al 1976and Kaul and Murthy 1985.…”
mentioning
confidence: 99%
“…In such cases, the term meta-anaphase is used as coined by Person (1955). The spontaneous occurrence of such plants showing high frequency of univalent chromosomes and associated meiotic irregularities during male meiosis is already known in other plant species (Kaul andMurthy 1985, Singh 2002). These plants showing abnormal synaptic behaviour during the earlier stages of meiosis I are generally classified into 2 categories on the basis of their effects on homologous chromosome pairing.…”
Section: Resultsmentioning
confidence: 99%